Evaluation of the Health Service Administration System in Improving Service Quality at the Bontonompo 1 Health Center, Gowa Regency - Satria Perdana; Rika, Rika (Jurnal EduHealth, 2025)
Health service administration is an important foundation in supporting the quality of services in primary health facilities such as community health centers. This study was conducted to evaluate the effectiveness of the administration system at the Bontonompo 1 Community Health Center in Bontoramba Village, South Bontonompo District, Gowa Regency, which includes aspects of efficiency, completeness of documents, utilization of information technology, staff competence, and patient satisfaction. This study aims to evaluate the health service administration system at the Bontonompo 1 Community Health Center in Gowa Regency. The evaluation was conducted based on several main indicators such as service efficiency, completeness of documents, utilization of information technology, staff competence, and patient satisfaction. The research method used was a quantitative descriptive approach with a survey approach to patients and community health center employees. The results showed that most indicators of administrative efficiency were classified as good, such as completeness of documents and the conformity of medical record data. However, problems arose in the long waiting time and the still low utilization of the digital patient information system. In addition, although the level of patient satisfaction with the friendliness and speed of service was quite high, the clarity of information and service flow still needed to be improved. Staff competence also indicated the need for further training, especially in the use of information technology and understanding of administrative regulations. It is recommended that improvements be made to the queue management system, strengthening of administrative HR training, and comprehensive implementation of information technology to improve the quality and efficiency of services.